Neonatal rat exposure to pyrethroid and organophosphate insecticides: A physiological and biochemical trial of progeny - Godinho, A. F. [UNESP]; Silva, D. A F [UNESP]; Mercadante, A. [UNESP]; Sartori, A. M A [UNESP] (My University, 2004)
A manufactured product (Ectoplus®) composed by a cypermethrin (44.7%) and dichlorvos (4.2%) mixture was administered (10mg/kg/day, orally, by gavage) to pregnant rats, during the periods of gestation+lactation, gestation, and lactation. Control mothers received vehicle aqueous solution during the gestation+lactation period. With the progeny, in the 1-15 post-natal days (PNDI-15) there were observed alterations in the periods of occurrence of teeth, hair, unfolding of ears, and in the developmental period for following reflexes: postural, palmar grasp, negative geotaxis, and acoustic startle reflex. After weaning (PND21), there were observed the presence of cypermethrin and dichlorvos in the blood brain and liver; decrease in weight of liver, of cholinesterase activity in the plasma, liver, and brain, and hepatic metabolizing activity of drugs; alterations of levels of gamma glutamyl transferase enzymes, of creatinine, and of potassium in the serum of the animals. In conclusion, neonatal exposure to a formulated mixture of cypermethrin and dichlorvos is inductive to alterations in characteristics that indicate somatic and neuromuscular development of the progeny, and in certain biochemical parameters. The results suggest that enzymatic assessment associated with somatic and neuromotor assessment can be important markers of developmental characteristics in neonatal toxicity by pesticide formulations based on mixtures of insecticides.
Keywords: Cholinesterase; Cypermethrin; Development; Dichlorvos; Hepatic drug metabolism; Insecticide exposure; cholinesterase; cipermethrin; creatinine; dichlorvos; gamma glutamyltransferase; organophosphate insecticide; potassium; pyrethroid; animal experiment; biochemistry; controlled study; developmental disorder; drug blood level; drug brain level; drug liver level; ear; ear unfolding; enzyme activity; enzyme analysis; grasping; hair growth; lactation; liver metabolism; liver weight; negative geotaxis reflex; nervous system development; neurologic examination; neuromuscular system; newborn; nonhuman; physical development; postnatal development; postural reflex; pregnancy; prenatal drug exposure; progeny; rat; reflex; startle reflex; tooth development; toxicity testing; weaning; xenobiotic metabolism